"This Program Helped Save Our Lives so We All Can Bond over That": A Preliminary Study of the First Oxford House Collegiate Recovery Home. Issue 4 (2nd October 2021) - Nguyen, Rebecca L.; Cope, Carlie E.; Wiedbusch, Elzbieta K.; Guerrero, Mayra; Jason, Leonard A.
ABSTRACT: College settings can be challenging environments for students recovering from substance use disorder. Collegiate Recovery Programs (CRP) have emerged on college campuses across the United States to help mitigate the risks recovering students face and to promote academic and recovery success. The current article describes the first collegiate recovery home to follow an Oxford House [OH] model, established at the University of North Carolina at Chapel Hill. In the present preliminary study, qualitative data were utilized to explore the strengths and challenges of this recovery model and students' experiences in the OH collegiate recovery home. Key stakeholders in the creation of this collegiate recovery home (n =2), as well as current and former student participants (n = 6), were interviewed. The key stakeholders' interviews revealed insights on the home's creation, modifications made from the traditional OH model, and the challenges faced in implementing a collegiate recovery home. Rapid qualitative analysis of the interviews of residents revealed salient themes that describe students' experiences within the collegiate recovery home: (1) resident social support, (2) connection to the student body, (3) anonymous status of the house, (4) lifestyle, (5) optimism, (6) self-independence, (7) Collegiate OH is essential for sobriety, and (8) UNC involvement and oversight. The implications of these findings for collegiate recovery homes are discussed, as well as suggestions for future studies.